Analysis of energy requirements and nutritional needs of rock climbing athletes - Hendra Mashuri; M. Adam Mappaompo; Didik Purwanto (Journal Sport Area, 2022)
Measuring the nutritional needs of rock climbing athletes can help athletes, coaches, and managers determine the portion of food and portion of the athlete's training. The purpose of this study is to determine the energy requirements and nutritional needs of FPTI rock climbing athletes in Buleleng Regency as recommendations for feeding. This research is a cross-sectional study that seeks to reveal quantitative variables and qualitative comments involving 12 rock climbing athletes. Data collection procedures by measurement of the nutritional needs of rock climbing athletes are carried out by providing an explanation of nutritional needs and measurement procedures, measuring BMI, calculating BMR and SDA, interviews for non-sports and sports physical activities, calculating total energy needs, determining food portions, and discussing the needs and eating of athletes per day. The calculation results show that the athlete's BMI is in the ideal category. The average energy requirement of athletes per day is 4568.45 calories. The average carbohydrate requirement for rock climbing athletes is 2741.07 calories or 685.27 grams. Energy needs that can be met by fat are 1142.11 calories or 126.9 grams. The energy requirement that can be supplied by protein is 685.27 calories or 171.32 grams. Rock climbing athletes require a diet with a rather low intake of protein and carbohydrates to keep body weight low. Adolescent rock climbing athletes must be careful in managing energy consumption which has an impact on growth and achievement.